Mixed ternary transition metal nitrides: A comprehensive review of synthesis, electronic structure, and properties of engineering relevance. (March 2019) - Tareen, Ayesha Khan; Priyanga, G. Sudha; Behara, Santosh; Thomas, Tiju; Yang, Minghui
Abstract: Ternary transition metal nitrides (TTMNs) have acquired substantial attention due to the ability to offer for tuning properties. Furthermore efforts to develop new TTMNs have resulted in the development of new syntheses approaches. In this review, recent progress made regarding investigations on electronic structure, stoichiometry, crystal structures, synthesis and applications are reviewed. Intermediate bonding in these solids exist in the structure types revealed so far. Bonding in these systems are an intriguing mix of ionic (oxide-like) and covalent (carbide-like). This enhances the possibilities of finding unique structures (i.e. anti-fluorite analogous [1]). A good case in point is the Delafosite types and η-nitrides structures found commonly in TTMNs which are typically associated with ABOx type oxides and carbides. Due to the rich structural chemistry associated with TTMNs, their study is considered a growing area in solid state and applied chemistry. Advancement made in the synthesis of powder and thin film materials of TTMNs are discussed. The powder methods involve the following methods: solid state, high-pressure-high temperature, solvothermal method, ammonothermal method, sol-gel method, Pechini method, temperature-programmed reduction, thermal degradation of metal complex, solid-state metal oxide-organic reaction, solid state ion exchange reaction, and electrodeposition replacement method. On the other hand, the TTMN thin film fabrication is based on two types of methods; physical vapor deposition (PVD) and chemical vapor deposition (CVD) method. The PVD involve deposition using different ways using laser or plasma based approaches (eg. pulsed laser deposition (PLD)) and magnetron sputtering. Chemical vapor deposition methods involve electrodeposition reaction method. Among all synthesis methods, the sol-gel process following the ammonolysis is considered comparatively better for large scale production owing to the simple apparatus setup. Different synthesis methods are deployable based on the application at hand. Applications can be range from electrocatalysts in ORR reaction [2, 3], electrocatalysts as sensor [4], supercapacitors [2, 3, 5], solar cell [6], magnetic, superconducting [7], hard coating materials [8] e.g. protective, functional, conductive, wear-resistance and decorative coating, NH3 synthesis [9], and hydrogenation process in hydrocarbon reactions [10].